Impact of COVID-19 on the change in work conditions and career choices in general Vietnamese population - Doan, Linh Phuong; Le, Linh Khanh; Dam, Vu Anh Trong; Vu, Thuc Minh Thi; Boyer, Laurent; Auquier, Pascal; Fond, Guillaume; Tran, Bach; Latkin, Carl A.; Ho, Roger C. M.; Ho, Cyrus S. H.; Zhang, Melvyn W. B. (Frontiers in Public Health, 2023)
Objectives The onset of COVID-19 has resulted in both morbidity and mortality. It also has a consequential impact on the Vietnamese economy. Prior studies have examined the impact of COVID-19 on healthcare professionals’ career decisions. However, no study remains to have examined the work conditions and career choices in a general Vietnamese population. Our study aims to identify factors associated with the change in work conditions and career choices in general Vietnamese population. Methods An online cross-sectional study between September 2021 through to November 2021 (during the Omicron COVID-19 pandemic). Snowball sampling method was utilised in recruiting the participants. The questionnaire used in this study included the following questions: (a) Socio-demographic information; (b) impact of COVID-19 on personal habits/daily expenses; (c) Current nature of work & impact of COVID-19 on work; (d) Impact of COVID-19 on career decisions. Data analysis was performed using STATA version 16. Descriptive analysis followed by Ordered logit regression was performed, to identify potential covariates. Results 650 participants were recruited, of which only 645 completed the survey. The completion rate was 99.2%. This study demonstrated the impact that COVID-19 has on finances, as only 32% of those sampled reported that they were able to pay in full. 46.6% of the respondents have had a decrease in their overall household income. With regards to their employment and work characteristics, 41.0% reported a decrease in their work satisfaction and 39.0% reported having reduced motivation for work. Females were less likely to consider transiting from their current job to another field than male participants. Respondents who were married, had a higher level of commitment to their current job, and lower inclination to transition to another field. Respondents experiencing financial difficulties were more likely to consider a transition to another field/work. Conclusion This is perhaps one of the first studies to have examined the impact of COVID-19 on work intentions regarding career choices and transitions in the general Vietnamese population. Future financial policies must take into consideration these factors.